EMOTIONAL IMPACT AND INMUNOLOGICAL CHANGES IN THE DIAGNOSTIC NOTIFICATION OF SEROPOSITIVITY - De Flores, Tomás (Anales de Psicología / Annals of Psychology)
The aim of this study is examine the adaptive response profile during a period of acute stress as a function of anticipation and reaction to positive HIV serostatus notification in prison inmates, according to the degree of relationship between immunomodulator phenomenon (deterioration of T lymphocytary response versus P.H.A.) and psychological and psychopathological variables. Subjects suffering of a psychiatric disease and those with the highest emotional reactivity showed an altered T-lymphocitary response at the beginning of the diagnostic report, followed by a slow and progressive recovery. The most sensitive measure of the influence of the emotional factors is the T lymphocytary response when stimulated by a marker of the cellular immunity. Anxiety and depression feelings follow a similar pattern. Altogether, emotional and immunological reactions follow a U curve.